Hubungan Antara Pengetahuan dan Sikap Perawat Terhadap Kepatuhan Dokumentasi Asuhan Keperawatan di RSUD Muntilan Ruang Rawat Inap Kabupaten Magelang - , HERDIANSYAH; , dr. Tahjono Kuntjoro, MPH, Dr.PH. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Medical record documentations must be accomplished because they contain memories used as source material for the accountability report of the hospital. Documentation shall be conducted in every medical service, especially by nurses providing nursing care. The significance of nursing care documentation can be viewed from several aspects, among which are the legal aspects, quality of service, communication, finance, education, research and accreditation. Evaluation and research on nursing documentation has not been implemented in Muntilan hospital, in fact nursing documentation is crucial in providing nursing care. Relevant research on nursing care documentation is, therefore, necessary. Objective: To determine the relationship between the knowledge and attitudes of nurses with their compliance in nursing care documentation. Method: This is an analytical research with quantitative and qualitative methods that employed cross sectional research design Results: The results demonstrated no significant correlation between knowledge and documenting compliance, R =- 0.061 and P = 0.581, attitude and documenting compliance also showed no correlation R = 0.013 and P = 0.904. Similarly, internal factors of nurses, such as education, years of service, type of employment and income outside of wages, did not affect the documenting compliance. In contrast, external factors such as nursing facilities, procedures, supervision and nursing care systems used might affect the compliance of nursing care documentation. Conclusion: No relationship was found between knowledge and attitudes of nurses with the compliance of nursing care documentation, nor was between the internal factors of nurses and the compliance documentation. However, external factors of nurses had influence on the compliance of nursing care documentation at Muntilan Hospital.